COMPREHENSIVE DIAGNOSIS AND TREATMENT OF CHRONIC PURULENT OTITIS MEDIA WITH COMPLICATIONS - Xatamov J.A; Xayitov A.A; Boltayev A.E; Davronov U.F (Scholar Express Journals, 2023)
The problem of timely diagnosis and adequate treatment of patients with chronic inflammation of the middle ear remains important for the otorhinolaryngological service. Domestic and foreign authors confirm that chronic purulent otitis media with complications is a serious disease that requires a comprehensive approach to diagnosis and treatment. The purpose of our study was to determine the strategy of comprehensive diagnosis and treatment for chronic purulent otitis media with complications. 36 patients with chronic purulent otitis media with complications who received treatment in the ENT department of the OMMC were connected.Samarkand. Among them are 8 patients with chronic purulent mesotimpanitis, 28 patients with chronic purulent epithympanitis. Of these, 29 patients with local complications (mastoiditis, labyrinthitis, facial nerve paresis), and 7 with intracranial complications (purulent meningitis, epidural abscess of the temporal lobe of the brain, sigmoid sinus synustrombosis). After surgical treatment, drainage of cerebral abscesses, removal of a blood clot from the sinus and intensive therapy, the condition of patients gradually improved, and normalization of clinical and biochemical parameters was observed, which allows an objective assessment of the effectiveness of treatment. The complex tactics of surgical and drug therapy carried out by us made it possible to improve the results of treatment of complicated chronic purulent otitis media.
Keywords: Mesotimpanitis; epitimpanitis; mastoiditis; complex